ANALISIS PENGARUH PROMOSI, SIKAP, REPUTASI DAN PELAYANAN AKADEMIK TERHADAP KEPUTUSAN MAHASISWA MEMILIH PRODI MANAJEMEN - Dedek Hari Supriani; Hidayat (Hirarki : Jurnal Ilmiah Manajemen dan Bisnis, 2019)
This study aims to determine the effect of promotion, attitude, reputation and academic services on the decision of students to choose the Management Study Program. The population of this study is the students of Management Study Program Faculty of Economics who registered from 2015/2016 to 2019/2020 around 777 students. The sampling method using accidental sampling and quota sampling techniques. The analysis technique used is multiple linear regression analysis using the SPSS program. The results of the study based on multiple linear regression analysis showed that promotions, attitudes, reputation and academic services had a positive and significant effect on the students’ decision to choose a Management Study Program with a coefficient of 0.389. Partially the variables that influence the decision to become a student are promotions, attitudes and academic services, while simultaneously the promotion variables, attitudes, reputation and academic services jointly influence the students’ decision to choose Management Study Program.